Comprehensive layout optimization of the transmission system in a deepwater wind farm cluster - Xu, Chang; Jiao, Zhixiong; Han, Xingxing; Huang, Yuwei; Wang, Jincheng; Zhang, Hu; Shen, Wen Zhong (Frontiers in Energy Research, 2023)
Compared to nearshore wind farms, deepwater offshore wind farms have better wind resources and broader development space, and will be the main trend of wind power development in the future. Due to the long distance from the shore, the investment and operation costs of the transmission system in a deepwater wind farm cluster are high and the electricity generated by the cluster is commonly transmitted by High Voltage Direct Current (HVDC) transmission technology to decrease power losses. For a given converter station, the comprehensive optimization of the layouts of the substations, AC export cables from the substation to the converter station, and cable arrays within each wind farm are complex and have not been well studied. This paper proposes a multi-level nested optimization strategy to minimize the total cost of the collection cables for a deepwater offshore wind farm cluster. The proposed method applies the Informed-RRT* method to optimize the layout of AC export cables while the cable arrays are layout by Prim's algorithm. During the optimization process, the gradient descent algorithm is used to optimize the positions of the substations, obtaining the transmission system scheme with the minimum cable investment. For a certain deepwater wind farm cluster, the total cable cost after optimization is reduced by 3.58%, which indicates the effectiveness of this method.